Ultrafast and ultra-parallel optoelectronics / edited by T. Sueta, T. Okoshi - Sueta, T.; Okoshi, T. (John Wiley & Sons, 1995)
Japan is at the forefront of research into optoelectronics, with the emphasis on ultrafast and ultra-parallel technologies. Many of the most active researchers in this field from Japanese universities have collaborated to produce this book. Their research was supported by the Grant-in-Aid for Scientific Research from the Ministry of Education, Science and Culture. Beginning with an overview of optoelectronics, ultrafast technologies are discussed in chapters on, for example, nonlinear optics, high speed photonic devices and large capacity optical communications. Ultra-parallel technologies are discussed in connection with such topics as optical computing, optical interconnection and image processing.